Toxin Neutralization Using Alternative Binding Proteins - Timothy Patrick Jenkins; Thomas Fryer; Rasmus Ibsen Dehli; Jonas Arnold Jürgensen; Albert Fuglsang-Madsen; Sofie Føns; Andreas Hougaard Laustsen (Toxins, 2019)
Animal toxins present a major threat to human health worldwide, predominantly through snakebite envenomings, which are responsible for over 100,000 deaths each year. To date, the only available treatment against snakebite envenoming is plasma-derived antivenom. However, despite being key to limiting morbidity and mortality among snakebite victims, current antivenoms suffer from several drawbacks, such as immunogenicity and high cost of production. Consequently, avenues for improving envenoming therapy, such as the discovery of toxin-sequestering monoclonal antibodies against medically important target toxins through phage display selection, are being explored. However, alternative binding protein scaffolds that exhibit certain advantages compared to the well-known immunoglobulin G scaffold, including high stability under harsh conditions and low cost of production, may pose as possible low-cost alternatives to antibody-based therapeutics. There is now a plethora of alternative binding protein scaffolds, ranging from antibody derivatives (e.g., nanobodies), through rationally designed derivatives of other human proteins (e.g., DARPins), to derivatives of non-human proteins (e.g., affibodies), all exhibiting different biochemical and pharmacokinetic profiles. Undeniably, the high level of engineerability and potentially low cost of production, associated with many alternative protein scaffolds, present an exciting possibility for the future of snakebite therapeutics and merit thorough investigation. In this review, a comprehensive overview of the different types of binding protein scaffolds is provided together with a discussion on their relevance as potential modalities for use as next-generation antivenoms.